Lithuanian teachers-scientists - Buckus , P. (Psichologija, 1973)
A number of Lithuanian teachers contributed to scientific research, devoted their lives to it. Many teachers of the republic have become doctors of sciences, professors, academicians. Mention is made in the article of former teachers, now candidates of sciences, docents, lecturers at higher educational establishments and associates of scientific research institutes. The article embraces the period from the 16th century to our days.